Effect of Job Satisfaction, Direct Compensation, Work Stress and Work Environment on Turnover Intention at PT. Indonesian Bamboo Craft - Arista Natia Afriany; Anisya Naryati; Anindita Imam Basri (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to examine the effect of job satisfaction, direct compensation, work stress and work environment on turnover intention at PT. Indonesian Bamboo Craft. This study uses quantitative methods with a sample of 80 respondents. The sampling technique in this study used non-probability sampling and the data collection method used a questionnaire. The results of the study show that job satisfaction has a negative and significant effect on turnover intention with a regression coefficient of -0.315 and a significance value of 0.025. Direct compensation has a negative and significant effect on turnover intention with a regression coefficient of -0.295 and a significance value of 0.017. Job stress has a positive and significant effect on turnover intention with a regression coefficient of 0.342 and a significance value of 0.000. The work environment has a negative and significant effect on turnover intention with a regression coefficient of -0.207 and a significance value of 0.028. Perceptions of job satisfaction, compensation, work stress and work environment simultaneously have a significant effect on turnover intention with a significance value of 0.000. therefore, all hypotheses are accepted. Keywords: ,, , , .